(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The article is aimed at improving knowledge on the subject Composition of students and teachers in the specialty "Visual Arts and Engineering Graphics". This article highlights such relevant forms of visual art as drawing and painting. Valuable scientific and methodological recommendations for organizing lessons in the visual arts and the acquisition of skills in performing compositions are given